21. Brain computed tomography combined with somatosensory evoked potentials in the prediction of brain death after cardiac arrest. Issue 12 (December 2017) - Scarpino, M.; Lanzo, G.; Lolli, F.; Moretti, M.; Carrai, R.; Spalletti, M.; Migliaccio, M.L.; Peris, A.; Amantini, A.; Grippo, A.
Abstract : Brain Death (BD) in coma after cardiac arrest (CA) is difficult to predict. Basal ganglia Gray Matter/White Matter (GM/WM) ratio density and Somatosensory Evoked Potentials (SEPs) may differentiate patients evolving toward BD. We used SEPs and brain computed tomography (CT) within the first 24 h after the coma onset. We measured the basal ganglia level GM/WM ratio in a group of 73 comatose CA patients with bilateral absence (AA) of cortical SEPs, or monolateral absence and a pathological response in the other hemisphere (AP). Of the 73 patients included in the study, 22 (30%) evolved toward BD. The GW/WM ratio predicted the BD (ROC area = 0.68, p  = 0.01). CT GM/WM ratio <1.07 had a sensitivity of 27%, a specificity of 96.2%, and a positive likelihood ratio of 6.91. In conclusion, SEPs and brain CT available within 24 h predict BD after CA. Severe SEP findings (SEP patterns AA, AP) identify a subset of patients in which BD can occur. Brain CT (GM/WM ratio in basal ganglia) predict an early evolution toward BD with a high specificity.